The emerging roles of MicroRNAs in autism spectrum disorders. (December 2016) - Fregeac, Julien; Colleaux, Laurence; Nguyen, Lam Son
Highlights: microRNAs (miRNAs) have important roles in development and function of the brain. Mutations of miRNA genes are associated with autism spectrum disorders (ASD). Twenty-six miRNAs are found deregulated in ASD by at least two independent studies. Several ASD genes are involved in miRNA biogenesis. miRNAs can potentially be used as biomarkers and therapeutic targets for ASD. Abstract: Autism spectrum disorders (ASD) are heritable neurodevelopmental conditions characterized by impairment in social interaction and communication and restricted, repetitive, stereotyped patterns of behavior. ASD likely involve deregulation of multiple genes related to brain function and development. MicroRNAs (miRNAs) are post-transcriptional regulators that play key roles in brain development, synapse formation and fine-tuning of genes underlying synaptic plasticity and memory formation. Here, we review recent studies providing genetic and molecular links between miRNA deregulation and ASD pathophysiology. These findings highlight the potential of miRNAs as both biomarkers and therapeutic tools in ASD.